An electro-mechanical straight alley for recording movement, position, and running time - Darnall, Joe W. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Conflict research using animals as subjects has typically been carried out with the straight alley. The experimental animal, usually a rat, is trained to run the alley and approach the goal box for positive reinforcement. After approach is well established, the subject is shocked in the goal box to bring about an avoidance response. These antithetical responses result in conflict, which is represented by the animal’s post-shock behavior in the alley. Two of the dependent variables observed are amount of movement and oscillation about a point. This requires continuous tracking of the location of the animal in the alley.